A Lumped Two-Compartment Model for Simulation of Ventricular Pump and Tissue Mechanics in Ischemic Heart Disease - Koopsen, Tijmen; Van Osta, Nick; Van Loon, Tim; Van Nieuwenhoven, Frans A.; Prinzen, Frits W.; Van Klarenbosch, Bas R.; Kirkels, Feddo P.; Teske, Arco J.; Vernooy, Kevin; Delhaas, Tammo; Lumens, Joost (Frontiers in Physiology, 2022)
Computational modeling of cardiac mechanics and hemodynamics in ischemic heart disease (IHD) is important for better understanding of the complex relations between ischemia-induced heterogeneity of myocardial tissue properties, regional tissue mechanics, and hemodynamic pump function. We validated and applied a lumped two-compartment modeling approach for IHD integrated into the CircAdapt model of the human heart and circulation. Ischemic contractile dysfunction was simulated by subdividing a left ventricular (LV) wall segment into a hypothetical contractile and non-contractile compartment, and dysfunction severity was determined by the non-contractile volume fraction (NCVF). Myocardial stiffness was determined by zero-passive stress length (L_(s0,pas)) and non-linearity (k_ECM) of the passive stress-sarcomere length relation of the non-contractile compartment. Simulated end-systolic pressure volume relations (ESPVRs) for 20% acute ischemia were qualitatively compared between a two- and one-compartment simulation, and parameters of the two-compartment model were tuned to previously published canine data of regional myocardial deformation during acute and prolonged ischemia and reperfusion. In six patients with myocardial infarction (MI), NCVF was automatically estimated using echocardiographic LV strain and volume measurements obtained acutely and six months after MI. Estimated segmental NCVF values at baseline and 6-month follow-up were compared with percentage late gadolinium enhancement (LGE) at 6-month follow-up. Simulation of 20% NCVF shifted the ESPVR rightward while moderately reducing slope, while a one-compartment simulation caused a leftward shift with severe reduction in slope. Through tuning of NCVF, L_(s0,pas) and k_ECM it was found that manipulation of NCVF alone reproduced the deformation during acute ischemia and reperfusion, while additional manipulations of L_(s0,pas) and k_ECM were required to reproduce deformation during prolonged ischemia and reperfusion. Out of all segments with LGE>25% at follow-up, the majority (68%) had higher estimated NCVF at baseline than at follow-up. Furthermore, baseline NCVF correlated better with percentage LGE than did NCVF at follow-up. We successfully used a two-compartment model for simulation of ventricular pump and tissue mechanics in IHD. Patient-specific optimizations using regional myocardial deformation estimated NCVF in a small cohort of MI patients in the acute and chronic phase after MI while estimated NCVF values closely approximated the extent of myocardial scar at follow-up. In future